Nowelizacja ustawy o postępowaniu w sprawach nieletnich - Górecki, Piotr (Wydział Prawa i Administracji UAM, 1996)
The Author discusses ledal state after coming into force of the law of 19.06.1995 that amended the law of 26.10.1982 on penal proceedings in juvenile cases. Comparing changes accoplished in particular of the law the Author comes do conclusion that they are not satisfactory enough. The changes are mostly fragmentary and are of repressive character. On the other hand one must approve the amendment of the articles 8 and 64 par. 1 of the old law as well as the introducing of new disposition which allows to stay the proceedings when a juvenile hides or it is impossible to detain him.
Amendment of the law on penal proceedings in juvenile cases